(untitled) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2021)
The purpose of this work is to analyze the vertical coordination in the pig production chain of Lara state for the year 2017, making use of the neo-institutional economic theory, since it establishes that the exchange of products and services can be carried out through of three modalities: open market, vertical integration and contracts. With this, it is intended that the agents involved know the factors that affect it and can establish measures that serve as a basis for the development of the sector. To achieve this objective, the methodology of "grounded theory" was used, which proposes to carry out a theoretical sampling for the collection of information, interviewing key personnel of the sector in the state, and achieving with them the theoretical saturation, which It was analyzed through a coding of the study variables. In this way, it was determined that independent producers work under the open market mechanism; while integrating companies are coordinated through vertical integration. Regarding transaction costs, integrating companies incur higher costs than independent producers; This, due to the greater frequency of their transactions and the amount of specific assets involved, thus being the determining factor in the vertical coordination mechanism used by each one. In addition, there is greater uncertainty in the transactional environment in independent producers than in integrated companies.